2020
DOI: 10.1007/s00134-020-05939-1
|View full text |Cite
|
Sign up to set email alerts
|

Causes and predictors of early mortality in patients treated with left ventricular assist device implantation in the European Registry of Mechanical Circulatory Support (EUROMACS)

Abstract: The aim of the study was to analyze early mortality after continuous-flow left ventricular assist device (LVAD) implantation which remains high. Methods: We analyzed consecutive (n = 2689) patients from the European Registry for Patients with Mechanical Circulatory Support (EUROMACS) undergoing continuous-flow LVAD implantation. The primary outcome was early (< 90 days) mortality. Secondary outcomes were differential causes of early post-operative death following LVAD implantation. Results: Univariable and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…Akin et al . found that ischaemic cardiomyopathy was more common in patients who died within 90 days after LVAD implantation when compared with other cardiomyopathies 12 . This suggested a possible worse prognosis for patients with ischaemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Akin et al . found that ischaemic cardiomyopathy was more common in patients who died within 90 days after LVAD implantation when compared with other cardiomyopathies 12 . This suggested a possible worse prognosis for patients with ischaemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 93%
“…Akin et al found that ischaemic cardiomyopathy was more common in patients who died within 90 days after LVAD implantation when compared with other cardiomyopathies. 12 This suggested a possible worse prognosis for patients with ischaemic cardiomyopathy. However, 1 year survival of patients with ischaemic and dilated cardiomyopathy was not significantly different in a retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…These causes of death are not particularly device‐specific, and therefore, are most likely related to patient medical history or patient management. For example, Sabashnikov et al found that higher preoperative central venous pressure and older age were the only independent risk factors for early mortality after CF‐LVAD implantation 21 ; and Ankin et al found several demographic (age, race, gender, and INTERMACS class), laboratory and hemodynamic variables that independently predict early mortality 22 . However, the current study’s analysis found that HM3 patients demonstrated a significantly lower in‐hospital mortality ( P = .03) than HW patients following CF‐LVAD exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The univariate analysis revealed that the female gender is one of the independent mortality predictors. 24 …”
Section: Discussionmentioning
confidence: 99%